Electrochemical and Plasmon‐induced Grafting of n‐Dopable π‐Conjugated Oligomers. Issue 13 (1st July 2021) - Bastide, Mathieu; Frath, Denis; Gam‐Derouich, Sarra; Lacroix, Jean‐Christophe
Abstract: The functionalization of electrodes by the reduction of diazonium cations generated in situ from 4‐(2, 3‐diethylthieno[3, 4‐b]pyrazine‐5‐yl)aniline has been investigated. The thienopyrazine unit of this molecule is a precursor of n‐dopable π‐conjugated oligomers. Electrochemical reduction of diazonium cation coats the electrode with organic layers. Raman, IR, and XPS analyses show that their composition corresponds to that of the starting monomer, while AFM scratching measurements indicate thicknesses below 10 nm. The electrochemical responses of various reversible redox couples on the modified electrodes show that the attached layer is insulating in the positive potential range but can be n‐doped at negative potential and switches to a conductive state. Moreover, oligo(4‐(2, 3‐diethylthieno[3, 4‐b]pyrazine‐5‐yl)phenyl) can be selectively grafted onto gold nanoparticles (AuNPs) by plasmon‐induced diazonium reduction. A 10–20 nm‐thick organic layer is easily grafted onto each gold nanoparticle by visible‐light illumination in a few minutes without any reducing agent or molecular photocatalyst. This result is attributed to the transfer of hot electrons from the excited plasmonic NPs to the diazonium, confirms that localized surface plasmon resonance can induce nanolocalized electrochemical reactions, and contributes to the emerging field of "plasmonic electrochemistry". Abstract : Electrodes are functionalized by electrochemical reduction of the diazonium cation from 4‐(2, 3‐diethylthieno[3, 4‐b]pyrazine‐5‐yl)aniline with ultrathin organic layers incorporating thienopyrazine units. This layer can be n‐doped while being covalently grafted to the surface. Moreover, it can be deposited onto gold nanoparticles (NPs) by plasmon‐induced diazonium reduction, thanks to the transfer of hot electrons from the excited plasmonic NPs to the diazonium salt. This confirms that localized surface plasmon resonance can induce nanolocalized electrochemical reactions.